Negative Symptoms in Schizophrenia: Where We have been and Where We are Heading. (16th June 2014) - Azorin, Jean‐Michel; Belzeaux, Raoul; Adida, Marc
Summary This review traces the history of negative symptom profiles in neuropsychiatry from their earliest emergence in the 19th century to the current psychiatric concepts and therapeutic approaches. Recent investigations performing exploratory and confirmatory factor analysis have suggested that negative symptoms are multidimensional, including evidence for at least two distinct negative symptom subdomains: diminished expression and amotivation. Preliminary studies have demonstrated the clinical validity of this distinction. Several potential pathophysiological validating factors based on brain imaging analysis of emotional experiences and expressions in individuals with schizophrenia are examined. Finally, the potential of different treatment strategies, including medications and various psychotherapeutic techniques, to most favorably treat each of these subdomains is discussed.